Pendampingan Penyusunan Laporan Keuangan Masjid Jamiatul Huda Ketaping Kota Padang - Handayani, Desi; Jr, Syafira Ramadhea; Harmen, Fauzi (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Mosques, as non-profit organizations, receive donations from the community. Takmir, as administrators and managers of mosque funds, must be accountable for the use of these funds in a transparent manner. This service partner is the Jamiatul Huda Ketaping Mosque, Padang City. So far, the mosque has carried out bookkeeping, but still in a simple way, and has not prepared financial reports according to ISAK 35 for Non-Profit Entities in accordance with currently applicable financial accounting standards. This community service aims to aid in the form of guidance and training in preparing mosque financial reports according to ISAK 35 using Microsoft Access. As a result, mosque administrators (Takmir and Treasurer) can prepare their financial reports according to the standards of ISAK 35, so that financial reports are more reliable, transparent, and accountable, as well as timely and easier after using Microsoft Access.